Comparative analysis of mental and physical fatigue on motor coordination, visual search patterns, perceived effort, and performance outcomes in closed-loop aiming task - Maryam Khalaji; Parvaneh Shamsipour Dehkordi; Fatemehsadat Mousavian; Saeed Alboghebeish (PLoS ONE, 2025)
This study has investigated the effects of both mental and physical fatigue on visual search patterns, motor coordination, perceived exertion, and performance accuracy while executing the golf swing. Thirty female recreational golfers with no professional experience in golf, aged 21.70 ± 2.21, underwent both mental and physical fatigue protocols in two separate conditions. In addition to the radial error, swing accuracy, Quiet Eye Duration (QED), and fixation number were recorded before and after fatigue. The results showed that mental fatigue significantly decreased QE duration (Mean difference = −138.75 ms, p = .0009) and fixation duration (Mean difference = 67.50 ms, p = .001), indicating a detrimental effect on sustained attention. Physical fatigue led to more fixations (Mean difference = 1.18, p = .05), reflecting compensatory visual strategies, but had a moderate negative impact on QE duration (Mean difference = −161.45 ms, p = .0002). Correlation analysis revealed a negative association between QE duration and swing accuracy under fatigue conditions (r = −0.71, p < .05 for mental fatigue and r = −0.49, p < .05 for physical fatigue), highlighting the role of sustained attention in motor performance. These findings demonstrate distinct cognitive and motor mechanisms underlying the effects of mental and physical fatigue, with implications for optimizing training and recovery strategies in sports.